India and the World - Ghosh, Ramesh Chandra (Calcutta, 1970)
"India and the World" is a collection of letters written by me between July 1950 and February, 1968. The book has been divided into two parts: the first part contains letters on current international problems, and the second, on present consti tutional issues. The introduction to the first part is virtually a reproduction of a lecture on India's Foreign Policy, delivered by me to the members of the Government of India Tourist Office, Calcutta, on September 26, 1969. I will not deny that these letters constitute a very heterogeneous assortment. Some letters marked with an asterisk were not published by the editor concerned for reasons best known to him. It is for the readers to judge whether they are worth the paper here printed on.
Keywords: International Relations